TP5.2.1 Duplex ultrasound should be interpreted with caution in vascular access. (28th October 2021) - Wicks, Andrew; De Siqueira, Jonathan; Bailey, Marc; Troxler, Max; Scott, Julian
Abstract: Aims: Dysfunctional vascular access in haemodialysis has varied clinical presentations, including prolonged bleeding, pain, loss of thrill, difficulties needling and ineffective dialysis. We aimed to establish whether specific presentations correlate with a higher frequency of adverse imaging findings and intervention. Methods: Duplex ultrasound scans (DUS) of surgical AV fistulae and grafts performed in a teaching hospital trust between 01/07/2019 and 31/01/2020 were analysed. Referral reasons, diagnostic findings, onward imaging and interventions to salvage fistulae and grafts were cross-referenced from electronic patient databases. Results: 359 scans of AV fistulae were performed in the period studied, of which, 220 were performed on men. Median age was 63 years (IQR 49-72). The most common referral reasons were loss of thrill and difficulty needling (n = 46, both). 185/359 (52%) scans lead to subtraction angiography and 46/359 (13%) to open surgical intervention. Median time from DUS to angiography was 21 days and 21% (39/185) of DUS did not match with angiographic results. When assessing outcomes based on presentation, 16/19 (85%, p  < 0.01) patients who had high venous pressures on dialysis and 23/31 (74%, p  < 0.01) of those with dialysis recirculation required endovascular intervention. Pain on dialysis correlated poorly with future intervention (6/30). Conclusions: A substantial proportion of DUS of dysfunctional vascular access do not correlate with subtraction angiography. Referral for DUS prior to angiography may delay intervention. Patients with objective signs of dialysis dysfunction (recirculation and high venous pressure) are highly likely to need intervention. Such cases may benefit from proceeding directly to angiography and on-table intervention.